HF‐Free Boc Synthesis of Peptide Thioesters for Ligation and Cyclization. (6th October 2016) - Raz, Richard; Burlina, Fabienne; Ismail, Mohamed; Downward, Julian; Li, Jiejin; Smerdon, Stephen J.; Quibell, Martin; White, Peter D.; Offer, John
Abstract: We have developed a convenient method for the direct synthesis of peptide thioesters, versatile intermediates for peptide ligation and cyclic peptide synthesis. The technology uses a modified Boc SPPS strategy that avoids the use of anhydrous HF. Boc in situ neutralization protocols are used in combination with Merrifield hydroxymethyl resin and TFA/TMSBr cleavage. Avoiding HF extends the scope of Boc SPPS to post‐translational modifications that are compatible with the milder cleavage conditions, demonstrated here with the synthesis of the phosphorylated protein CHK2. Peptide thioesters give easy, direct, access to cyclic peptides, illustrated by the synthesis of cyclorasin, a KRAS inhibitor.